2014
DOI: 10.1371/journal.pone.0103262
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence of Plasmodium vivax Mono and Mixed Malaria Parasite Infections in Duffy-Negative Native Cameroonians

Abstract: The malaria parasite Plasmodium vivax is known to be majorly endemic to Asian and Latin American countries with no or very few reports of Africans infected with this parasite. Since the human Duffy antigens act as receptors for P. vivax to invade human RBCs and Africans are generally Duffy-negative, non-endemicity of P. vivax in Africa has been attributed to this fact. However, recent reports describing P. vivax infections in Duffy-negative Africans from West and Central parts of Africa have been surfaced incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 34 publications
(79 reference statements)
7
50
0
1
Order By: Relevance
“…It is also consistent with studies which show that P. falciparum was associated with all the cases of clinical malaria in the country [15–17]. The finding is however contradictory to studies that have reported prevalences of P. vivax ranging from 4% [14] to 14.9% [13]. The difference between these studies and ours could be attributed to differences in the study design; our study targeted children presenting with symptoms of malaria meanwhile theirs targeted both symptomatic or asymptomatic adults and children.…”
Section: Discussionsupporting
confidence: 89%
“…It is also consistent with studies which show that P. falciparum was associated with all the cases of clinical malaria in the country [15–17]. The finding is however contradictory to studies that have reported prevalences of P. vivax ranging from 4% [14] to 14.9% [13]. The difference between these studies and ours could be attributed to differences in the study design; our study targeted children presenting with symptoms of malaria meanwhile theirs targeted both symptomatic or asymptomatic adults and children.…”
Section: Discussionsupporting
confidence: 89%
“…Plasmodium falciparum was identified as the only species causing malaria in the target population, which is in line with the study by Kwenti et al [7], but contradictory to the study by Mbenda and Das [30] in which a prevalence of 4% for P. vivax infection was reported in YaoundĂ©. The differences in the study design may account for this discrepancy; our study targeted mainly children meanwhile theirs targeted adults and children.…”
Section: Discussionsupporting
confidence: 63%
“…Duffy genotype was assessed by sequencing the ~516 bp region of the gene encoding Duffy antigen as previously described [12, 24]. PCR products were sequenced by MWG Eurofins (Germany).…”
Section: Methodsmentioning
confidence: 99%
“…To date, this has been mainly accounted for by the absence of the red blood cell surface Duffy antigen among Africans living in this area [4]. Meanwhile, however, P. vivax infections were documented in Duffy-negative subjects in Brazil [5, 6], Ethiopia [7, 8], Madagascar [9], but also in West African countries, such as Mauritania [10], Cameroon [11, 12], Equatorial Guinea, and Angola [13]. According to these different studies, the prevalence of P. vivax in West-Africa is probably underestimated and large-scale epidemiological studies are thus required to investigate the burden of P. vivax infections [3].…”
Section: Introductionmentioning
confidence: 99%